The occurrence of resveratrol in foodstuffs and its potential for supporting cancer prevention and treatment. A review - Ewa Dybkowska; Anna Sadowska; Franciszek Świderski; Rita Rakowska; Katarzyna Wysocka (National Institute of Public Health - National Institute of Hygiene, 2018)
Over recent years, there has been increasing interest noted in those active substances derived from plants that show potential for preventing cancer development. The most promising candidate is resveratrol which can be found in large amounts in the skin of grapes, tomatoes and in red wine. Its beneficial effects on the human body are seen both in prevention and therapy. The anti-carcinogenic action of resveratrol is linked with its ability to neutralise reactive oxygen species and to modulate cellular processes such as apoptosis, and both cancerous cell proliferation and differentiation. This article presents the characteristics of resveratrol as a bioactive compound derived from natural sources exhibiting anti-cancer properties, which, because of a wide spectrum of biological activities may be used in the prevention of cancer. Many in vitro and animal-based studies have demonstrated such preventative anti-cancer action in the colon, prostate, breast and lungs. The beneficial effects of resveratrol are also presented when adopted as a support to conventional treatments of cancer using chemo- and radio-therapy.